WordPress System for Information Centers - Göksoy, Rıza Burak (Information World, 2011)
Developing web technologies enabled realizing many activities which required information, experience, and hard work or are time consuming, and costly in the near past. For example nowadays to create an internet website, to update it, to acquire a subdomain name and make the site interactive with users can be easily done either cost free or rather with low cost. Systems such as WordPress, ensure to create blog/internet website by sub-domain method and give required technical support to people by their admin panels. These facilities provide new oppurtunities such as communicating with users on the web interactively, obtaining statistical data and publicizing the organization, for information centers.In addition to this, WordPress system with user oriented dynamic blog structure, offers oppurtunities like marketing services to information centers which already have a website.In this study WordPress system will be explained in the context of its installation, by subdomain method and its main attributes which provide communication with users, marketing their organization and services for information centers.
Keywords: Blogs; Information centers; Libraries; Web 2.0; Library 2.0